(NsKOROSTNOE TO^ENIE (B/s - (NwULXF(B, (Na(B.(Nm(B.s; (NwULXF(B, (Na(B.(Nms; (N{IFRIN(B, (Na(B.(N{s; (N{ACMAN(B, (Ni(B.(Nm(B.s ((NmOSKWAs (NlENINGRAD (B:s (NmA[GIZ(B,s, 1948)
(NzAKL(B. : (NS(B. 126-132s
(NpRILOV(B. : (NS(B. 133-141s
(NlIT(B. : (NS(B. 142-143s
Keywords: (NrEZANIE METALLOWs